Market Reaction to Government Policy for Implementation of Biodiesel Mixture Proportion to Palm Oil Plantation Issuers - Muhammad Ivan Ardhiansyah; Agus Munandar (Jurnal SEKURITAS (Saham, Ekonomi, Keuangan dan Investasi), 2023)
This research attempts to make investors in palm oil plantation capital market can take appropriate action on their portfolios if in the future the government issues a policy of implementing biodiesel. The manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2019 served as the study object. Purposive sampling was utilized in sample selection, yielding 15 samples. The research conducted is quantitative with the Single Index Model (SIM) method were the analytical techniques used in this study, with the SPSS 25 program being used for the t-test. The analysis results indicated that mandatory B30 implementation have a significantly different impact between before and after the announcement. The study's findings offer insight and input for palm oil plantation company management that the next mandatory is good news. The findings of this study should be helpful to investors how to implement action in the capital market. This study uses samples were taken without regard to the size of the company based on market capitalization and the number and class of investors, and the domestic CPO price variable only takes one price point.